Math, asked by Rishijain1390, 5 months ago

Simplify and solve the given equation linear equation 15(y – 4) – 2(y – 9) + 5(y + 6) = 0

Answers

Answered by SparklingThunder
2

\huge\purple{ \underline{ \boxed{\mathbb{\red{QUESTION : }}}}}

\small \textsf{Solve: 15 ( y -  4) - 2  ( y - 9) + 5 ( y + 6 ) = 0}

\huge\purple{ \underline{ \boxed{\mathbb{\red{ANSWER : }}}}}

 \large\displaystyle { \color{red} \sf y =  \frac{2}{3} }

\green{ \large \underline{ \mathbb{\underline{GIVEN : }}}}

 \textsf{15 ( y -  4) - 2  ( y - 9) + 5 ( y + 6 ) = 0}

 \green{ \large \underline{ \mathbb{\underline{TO  \: FIND : }}}}

 \red{   \overline\textsf{\underline{Value of y .}}}

 \green{ \large \underline{ \mathbb{\underline{SOLUTION: }}}}

   \begin{array}{l} \\ \hline  \\ \small \sf{15 ( y -  4) - 2  ( y - 9) + 5 ( y + 6 ) = 0} \:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\\   \\\small \sf15y - 60 - 2y + 18 + 5y + 30 = 0 \\  \\  \small \sf15y - 2y + 5y - 60 + 18 + 30 = 0 \\  \\ \small \sf13y + 5y - 60 + 48 = 0 \\  \\ \small \sf18y - 12 = 0 \\  \\ \small \sf18y = 12 \\  \\ \small  \displaystyle\sf y =  \frac{12}{18}  \\  \\ \small  \displaystyle\sf y =  \frac{2}{3}  \\   \\  \hline\\  \end{array}

Answered by shaswat8080
0

Step-by-step explanation:

given equation is that

15(y - 4) - 2(y - 9) + 5(y + 6) = 0

solution

simplify by solving brackets

15(y - 4) - 2(y - 9) + 5(y + 6) = 0

15y - 60- 2y  + 18 + 5y + 30 = 0

add the numbers

15y - 12 - 2y + 5y = 0

combine like terms

18y - 12 = 0

add 12 to both side of equation

18y - 12 + 12 = 0 + 12

simplify

we get

18y = 12

by solving we get

y =  \frac{12}{18}  =  \frac{2}{3}

hence value of variable y is 2 by 3.

Similar questions